# Re: I don't see what I am doing wrong

[ Follow Ups ] [ Post Followup ] [ Main Message Board ] [ FAQ ]

Posted by Lisa on October 11, 2002 at 14:45:15:

In Reply to: Re: I don't see what I am doing wrong posted by Brad Paul on October 11, 2002 at 07:39:41:

t= ln 1 = 0
and you are right, I got confused. Formatting is very good. Thanx :)
: : (e^(2t))-(3e^t)+2=0
: : let x =e^t
: : so (x^2)-(3x)+2=0
: : (x-2)(x-1)
: : ((e^t)-2)((e^t)-1)
: : so ln^(et) = ln2
: : and ln^(et) = 1
: : and that is wrong, the answer is suppose to be 0 and ln2
: : What did I do wrong?

: So close!

: Let me start at:

:
: (et-2)(et-1)=0

: Note You left out the =0. When you work problems always make sure that
: everything that is written down is a complete true statement. It will
: help you come back and study the problem letter.

: I will break the equation in to two parts but I will only do one part:

: (et-2)=0

: et=2

: ln{et}=ln{2}

: Note ln{et}=t therefore:

: t=ln{2}

: Now you do:

: (et-1)=0

Name:
E-Mail:

Subject:

Optional Image URL:

[ Follow Ups ] [ Post Followup ] [ Main Message Board ] [ FAQ ]